2009
DOI: 10.1002/anie.200901059
|View full text |Cite
|
Sign up to set email alerts
|

A Single α‐Helical Turn Stabilized by Replacement of an Internal Hydrogen Bond with a Covalent Ethylene Bridge

Abstract: Walking the carbon bridge to helix stabilization: α‐Helix mimetics have been synthesized that contain an ethylene linkage in place of an (i,i+4) hydrogen bond (see structure). The smallest unit possible, a modified pentapeptide, shows the characteristic features of a helix (see CD spectrum). Incorporation of this carbon bridge into a peptide represents the first example of replacement of an internal backbone hydrogen bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The peptide conformation can be affected by the configuration of atoms not only within but also outside of the peptide backbone . Therefore, we hypothesized that cyclic peptides tethered by diacids of different substitution types might provide a library for an optimal nucleating template.…”
Section: Methodsmentioning
confidence: 99%
“…The peptide conformation can be affected by the configuration of atoms not only within but also outside of the peptide backbone . Therefore, we hypothesized that cyclic peptides tethered by diacids of different substitution types might provide a library for an optimal nucleating template.…”
Section: Methodsmentioning
confidence: 99%
“…For a-peptides, the most common strategy for helix stabilization involves the covalent linking of adjacent turns of the helix with lactam, [17] triazole, [18] alkyl, or hydrazone bridges. [19,20] It was found that cyclization of a b-peptide [21] or a strategically placed salt bridge or disulfide linkage between residues i and i + 3 along the chain of residues of a 3 14 -helix [22,23] could lead to greater stability of the helix. It has further been reported that an amide-bond linker between b-amino acid residues in the i and i + 3 positions also increases the degree of 3 14 -helicity in H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In conclusion, we have isolated and characterized au nique natriuretic peptide from T. carinatus.T he mature 31 residue peptide contains am ucin-type Gal-GalNAc Olinked glycan on the C-terminal threonine residue.NMR and CD analysis identified an a-helical secondary structure in both synthetic glycosylated and nonglycosylated NPs and may prove invaluable in determining the full natriuretic peptide pharmacophore to aid the design of smaller helical mimetics. [29,30] While NMR structural analysis and stability testing did not infer astructural role for the glycan, the cGMP assay showed both variants are bifunctional in stimulating both NPR-A and NPR-B in af ashion similar to that of the designed chimera CD-NP.T hus,T cNPa represents the first report of an onhuman O-glycosylated NP which is bifunctional and serves as al ead molecule to an ovel therapeutic class.…”
Section: Methodsmentioning
confidence: 97%
“…[13] Synthetic forms of ANP (Carperitide) and BNP (Nesiritide) are approved for the treatment of acute decompensated heart failure in Japan and the US,r espectively, though both have been linked with unwanted side effects such as excessive hypotension and impaired renal function. [29,30] While NMR structural analysis and stability testing did not infer astructural role for the glycan, the cGMP assay showed both variants are bifunctional in stimulating both NPR-A and NPR-B in af ashion similar to that of the designed chimera CD-NP.T hus,T cNPa represents the first report of an onhuman O-glycosylated NP which is bifunctional and serves as al ead molecule to an ovel therapeutic class. .…”
Section: Methodsmentioning
confidence: 98%